Optimization of ultrasound assisted extraction of sappan (Caesalpinia sappan L) wood for preparation of high quality extract - Djaeni, Moh; Budi Sasongko, Setia; Yuni Susanti, Devi; Mahatmanti, F Widhi; Cahyo Kumoro, Andri; Kurniasari, Laeli (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This study optimized the Ultrasound-Assisted Extraction (UAE) of sappan wood (Caesalpinia sappan L.) using Central Composite Design-Response Surface Methodology (CCD-RSM) and investigated its kinetics. Temperature, solvent-to-solid ratio, and extraction time were selected as independent variables with extract yield as the response. Analysis of Variance (ANOVA) showed that the solvent-to-solid ratio significantly affected yield. Optimal extraction conditions were 69.9°C, 29.9 mL/g, and 20.2 min, producing approximately yield of 0,293 mg GAE/g sample. High Performance Liquid Chromatography (HPLC) confirmed the presence of brazilin, while Fourier Transform InfraRed (FTIR) analysis indicated the retention of functional groups. UAE was shown to enhance extraction efficiency and preserve phenolic compounds. Additionally, the extraction process was modeled, resulting in a validated effective diffusivity (De) of 1.8 × 10?? cm²/s, The kinetic study was useful in industrial application especially to determine appropriate extraction time.